Assisting the Investigation of Stranger Rapes: Predicting the Criminal Record of U.K. Stranger Rapists From Their Crime Scene Behaviors. Issue 3 (February 2021) - Almond, Louise; McManus, Michelle; Bal, Amarat; O'Brien, Freya; Rainbow, Lee; Webb, Mark
Davies, Wittebrood, and Jackson (1997) were among the first to investigate whether offense behaviors are predictive of criminal history, with the findings of their paper then utilized by the National Crime Agency (NCA) Behavioral Investigative Advisors (BIAs) when assisting rape investigations. The aim of the study was to replicate this seminal paper with a larger contemporary sample of U.K. stranger rapists as identified by NCA. Data from 474 adult male stranger rapists were obtained in relation to 22 crime scene behaviors and nine preconviction variables. Results indicated significant differences between the Davies et al. original data set and this contemporary data set in both the behaviors and the preconvictions they displayed. The contemporary sample was significantly less likely to use sighting precautions, use violence, and take fingerprint precautions. This sample was also significantly less likely to have any of the preconviction crime types, with the exception of drugs offenses. When exploring the current data set of stranger rapists, statistical analyses indicated a number of key offense behaviors that were able to predict the criminal history of stranger rapists. However, contrary to previous research, no behaviors were found to be associated with sexual offense preconvictions. The results highlight that behaviors and characteristics of stranger sex offenders have changed since the 1990s. The implications for practice are discussed.